PROTES JEPANG TERHADAP PENERAPAN UU NO. 4 TAHUN 2009 TENTANG MINERAL DAN BATUBARA INDONESIA TAHUN 2009 - Djamhur, Ulfa; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study discusses about the Japanese protest on Regulation of Law No.4 of 2009 on mineral and steel. the application of this law are applied on 12 January 2014 on the application of this law encountered many obstacles including protests from Indonesian mineral importing country. one that rejects namely Japan. this is because most of the japan minerals derived from the Indonesian. The results of this study are Japan protested the application of the law because it would be difficult for japan get a supply of minerals from indonesia. Japan also plans to bring this issue to wto on the basis of violation of GATTKeywords: mineral and coal constitution, mineral export policy and Japan protested